Combating international crimes in Iraqi legislation (Medico Legal Update, 2020)
The terrorist financing activities are considered one of the most important threats that facing the security andsafety of people of society in all its forms, as their danger increases by adopting a pattern of transnationalorganized crime. There is no longer planning, managing and implementing them is done within the territoryof one country, but its lines are woven across multiple countries to conduct them in the targeted countrywith the crime. Iraq comes in the forefront of countries that suffered from terrorism and the violent crimes,inorder to strike stability in it, also to sow discord and sectarian fighting for this, the Iraqi state must confrontthe terrorism in general, as well as the terrorist financing activities in particular, reducing its seriousness andpunish the perpetrators, so, the Anti-Terrorism Law No. 13 of 2005, and the Anti-Money Laundering andTerrorist Financing Law No. 39 of 2015, was issued, as it was issued in implementation of Article 22 ofthe Money Laundering Law that was mentioned previously,this leads to the question about the adequacy ofthese legal texts to address the crime of financing terrorism, whether the Iraqi legislator succeeded in puttingin place the necessary mechanisms with the appropriate part to prevent these funds for reaching to the handsof terrorist organizations.